Occupational Stress and Teachers’ Job Satisfaction: Implication to the Human Relations Management Approach - Abdul Majid, Izaidin; Kamarudin, Mohd Fauzi; Samroz, Mohd Zawaei (2008)
the aim of this study is to investigate the prevalence of teacher stress with special emphasize on the human relations management approach; to identify the stress factors and t examine the relationship between teacher stress and job satisfaction.